The Impact of Online Community on Farmer Empowerment: A Strategical Analysis for Development The Technology-to-Performance - Anton Susanto; Ali Agus; Jangkung Handoyo Mulyo; Hakimul Ikhwan (Eduvest - Journal of Universal Studies, 2022)
This research provides empirical evidence for the benefit of social media in the online farmer community. The benefit that focus on empowerment value. The case study is used to explore the ICT usage in the community of Laying Hens Farmer in East and Central Java implementing the multi-feed and additive supplement. The research develops The Technology-to-Performance Chain (TPC) approach to analysis the strategy of farmer empowerment. The performance that was addressed by empowerment values. The study results that the farmer’s empowerment are influenced significantly by task-technology fit with a path coefficient of 0,704. It means that utilization of social media as the online media of community will encourage empowerment if the information and knowledge sharing activities inside are related to the task or farmer's livelihood. The farmer's characteristics and the facilitating condition affect the empowerment insignificantly. However, the facilitating condition determines the task-technology fit with the path value 0,868. This study discusses 3 important layers in farmer empowerment strategies through online communities. The first is the underlying factors which includes internet access, product innovation and agents of change (facilitators/agricultural extensionists), the second is the adoption process (both internet adoption and product knowledge adoption) while the third is the impact of empowerment which is direct (output) and indirect (outcome).